KARAKTERISTIK TINDAK PIDANA PASAR MODAL - Sultan Syahril A Kh (Fakultas Hukum Universitas Narotama, 2022)
National economic goals that are able to grow stably and sustainably, create broad and balanced employment opportunities in all sectors of the economy, as well as provide equitable welfare to all Indonesians General explanation of Law No. 8 of 1995 concerningThe Capital Market (hereinafter referred to as the Capital Market Law) explicitly explained that